Morphological characterization of biominerals from five multicellular marine algae species - A. M. Zakharenko; M. A. Nawaz; V. V. Chaika; I. V. Zemchenko; T. Yu. Orlova; A. A. Begun; R. V. Romashko; A. N. Galkina; A. A. Karabtsov; G. Chung; K. S. Golokhvast (Труды по прикладной ботанике, генетике и селекции)
Silica biominerals are deposited as amorphous solid structures in plant cells and tissues, providing rigidity to different plant parts and assisting in defence. The shape and size of phytoliths are well established and serve as a useful tool in taxonomic analyses. For the first time we extracted and studied silica biominerals of five marine macroalgae, which we observed by light microscopy, scanning electron microscopy, and X-ray diffraction analysis (XRD). More than nine different morphotypes of phytoliths ranging from ≥ 10 to ≥ 350 μm in size were found. Some of them were phytoliths made of silica while others showed characteristics of different minerals of calcium. In our study, the “honeycomb” formations were only recorded in Laurencia tropica Yamada and pyramid tabular ones were found only in Tichocarpus crinitus (S.G. Gmelin) Ruprecht. The XRD analysis showed that they consisted of virgilite and gypsum substance, respectively. Silica phytoliths are intrinsic parts of the algae and their morphological characterization can provide the basis for palaeo-reconstruction and taxonomic investigation of brown and red algae in palaeontological studies of fossils where all organic matter has decayed.